A new occurrence of archosaur footprints from the Löwenstein Formation (Late Triassic, Middle Norian) of southern Germany. Issue 1 (2nd January 2022) - Wagensommer, Alexander; Porchetti, Simone D'Orazi; Bolter, Hans Dieter; Antonelli, Matteo; Haderer, Frank-Otto
Abstract: Two sandstone slabs from a new Norian tetrapod tracksite in the Löwenstein Formation of southern Germany preserve a set of tracks including both tridactyl and pentadactyl ichnites, referred to theropod dinosaur and sphenosuchian crocodylomorph trackmakers, respectively. A very large manus print hints at the presence of a hitherto unknown large quadrupedal archosaur in the Norian fauna of southern Germany. The material includes one of the oldest records of crocodylomorph tracks presently known, in agreement with the skeletal record from the same formation.